Men Devote More Time to Work, While Women Focus on Personal Life? - Tauraitė, Viktorija (Social Welfare: Interdisciplinary Approach, 2025)
The purpose of this study is to examine the empirical content of time allocation between work and personal life among men and women, identifying differences in the average daily time between the two genders. The theoretical aspects of time allocation are analyzed by using comparative literature analysis and summarization methods. Empirical research is conducted by using statistical data analysis, correlation analysis, non-parametric Mann-Whitney U test and data collection methods: survey, time diary and semi-structured expert interview. The target population of this study comprises self-employed individuals in Lithuania.The results indicate that, from a gender perspective, men allocate most of their daily time to personal life; sleep; other physiological needs; leisure (in a narrow sense); and travel, while women allocate their time primarily to work; household; and family care. This means that women focus on work activities and activities related to the family (in terms of time). On the other hand, men devote more time per day to personal life. The article also examines scientific hypothesis H11: the average daily time allocated to work differs between self-employed men and women in Lithuania; this hypothesis has been rejected.
Keywords: time allocation; personal life; work; self-employed individuals; work-life balance